2020
DOI: 10.1021/acs.jctc.0c00621
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electronic Structure Modeling and Junction Structure on First-Principles Chiral Induced Spin Selectivity

Abstract: We have carried out a comprehensive study of the influence of electronic structure modeling and junction structure description on the first-principles calculation of the spin polarization in molecular junctions caused by the chiral induced spin selectivity (CISS) effect. We explore the limits and the sensitivity to modeling decisions of a Landauer/Green's function/two-component density functional theory approach to CISS. We find that although the CISS effect is entirely attributed in the literature to molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 162 publications
8
53
0
Order By: Relevance
“…[48,49] Recent first principles calculations for a chiral monolayer on a magnetic substrate provided first indications of an emergent electronic structure and emphasized the role of exchange interactions. [106] However, the emergent structure is generally expected and practically confirmed [34,107,108] to be sensitive to the choice of density functional and this effect was not investigated. In addition, chiral symmetry breaking was enforced "manually" via introduction of an external Ni atom, so that the effect of the intrinsic chirality remains to be clarified.…”
Section: Theory Of Ciss In Chemical Reactionsmentioning
confidence: 99%
“…[48,49] Recent first principles calculations for a chiral monolayer on a magnetic substrate provided first indications of an emergent electronic structure and emphasized the role of exchange interactions. [106] However, the emergent structure is generally expected and practically confirmed [34,107,108] to be sensitive to the choice of density functional and this effect was not investigated. In addition, chiral symmetry breaking was enforced "manually" via introduction of an external Ni atom, so that the effect of the intrinsic chirality remains to be clarified.…”
Section: Theory Of Ciss In Chemical Reactionsmentioning
confidence: 99%
“…In particular, it was found that the anisotropy factor of responsivity that describes the distinguishability to CPL is reported to be much larger than g abs , which could also be attributed to the CISS effect in chiral materials. The theoretical study of the CISS effect has also not been reported in a chiral perovskite yet, but theoretical models in other chiral systems for understanding the CISS effect have been reported. Among them, the nonequilibrium Green’s function (NEGF) technique with a model Hamiltonian is widely used to understand the spin-polarized transport; the results in double-stranded DNA, single-stranded DNA, and α-helical protein are in excellent agreement with experimental results. , …”
mentioning
confidence: 87%
“…A source of third terminal is, therefore, being looked for by several theoretical researchers. In order to overcome these problems, recent experiments and calculations suggest an involvement of phonons as a source of effective spin polarization [30][31][32][33] whereas others will try to include exchange interactions [34,35]. A model proposed here is another way to address this issue by explicitly including pseudo Jahn Teller effect into the system to include dynamics of chiral order parameter 𝐺𝐺 0 (object).…”
Section: Dynamics Of Chiral Order Parametermentioning
confidence: 99%